Diurnal Fluctuations in Plasma Hydrogen Sulfide of the Mice - Jin, Sheng; Tan, Bo; Teng, Xu; Meng, Ruoni; Jiao, Xin; Tian, Danyang; Xiao, Lin; Xue, Hongmei; Guo, Qi; Duan, Xiaocui; Wu, Yuming (Frontiers in Pharmacology, 2017)
Circadian rhythms are essential in a myriad of physiological processes to maintain homeostasis, especially the redox homeostasis. However, little is known about whether plasma H2S exhibits the physiological diurnal variation. The present study was performed to investigate the diurnal fluctuations of plasma H2S and explore the potential mechanisms. We found that the plasma H2S of the C57BL/6J mice was significantly higher at 19 o’clock than those at 7 o’clock which was not affected by the blood-collecting sequence and the concentrations of plasma cysteine (a precursor of H2S). No significant differences in mRNA or protein expression of the CSE, CBS, or MPST were observed between 7: 00 and 19: 00. There were also no significant differences in the CSE and CBS activities, while the activities of MPST in tissues were significantly higher at 19 o’clock. After treatment with AOAA (a CBS inhibitor) or PPG (a CSE inhibitor) for 14 days, plasma H2S concentrations at 19 o’clock were still significantly higher than those at 7 o’clock, although they were both significantly decreased as compared with controls. Identical findings were also observed in CSE KO mice. We also found the plasma H2O2 concentrations were significantly higher at 19 o’clock than those at 7 o’clock. However, H2O2 concentrations were significantly decreased at 19 o’clock than those at 7 o’clock when mice were exposed to continuous light for 24 h. Meanwhile, the diurnal fluctuations of plasma H2S levels and MPST activities in tissues were disappeared. After treatment with DTT for 14 days, there was no significant difference in plasma H2O2 concentrations between 7 o’clock and 19 o’clock. Meanwhile, the diurnal fluctuations of plasma H2S levels and MPST activities in tissues were disappeared. Identical findings were also observed in SOD2+/- mice. When heart tissues were incubated with increasing concentrations of H2O2in vitro, H2O2 could dose-dependently increase the activity of MPST within a certain concentration range. In conclusion, our studies revealed that plasma H2S concentration and tissue MPST activity exhibited diurnal fluctuations. Modulated by plasma H2O2 concentration, changes of MPST activity probably led to the diurnal fluctuations of plasma H2S.